Evaluasi Penerapan Kurikulum Merdeka Pada Pembelajaran Geografi Kelas X di SMA Negeri 1 Jakarta - Gloria Rebecca Estefan; Ilham Badaruddin Mataburu; Fauzi Ramadhoan (Universitas Maritim AMNI Semarang, 2023)
This research aims to determine the success of implementing the Merdeka Curriculum in the subject of geography, focusing on the following aspects: (1) Implementation of geography teaching hours, (2) Use of teaching materials, (3) Learning process, (4) Assessment process, (5) Student learning outcomes, and (6) Challenges faced. The method used in this research is descriptive with a quantitative approach. The population of the study consists of all 286 students in Grade X at SMA Negeri 1 Jakarta. The sample for this research is composed of 75 students and 1 geography teacher, selected using simple random sampling technique. Data collection is carried out through distributing a questionnaire containing 20 closed-ended statements. The results of this research obtained a percentage of 76%, which falls into the good category. The students' learning outcomes reached the Minimum Mastery Criteria (KKM) with an average score of 80.5. There are several challenges faced, such as students feeling overwhelmed by the number and difficulty of project assignments, which clash with their school tasks. They also feel burdened because the Merdeka Curriculum does not offer subject specialization, requiring students to take all subjects. The challenges faced by the teacher include a lack of experience in implementing self-directed learning. Additionally, time management is a challenge as the geography teacher at SMA Negeri 1 is the only one responsible for teaching Grade X, XI, and XII.